Different Multivariable Risk Factors for Rapid Progressive Interstitial Lung Disease in Anti-MDA5 Positive Dermatomyositis and Anti-Synthetase Syndrome - Zuo, Yu; Ye, Lifang; Chen, Fang; Shen, Yawen; Lu, Xin; Wang, Guochun; Shu, Xiaoming (Frontiers in Immunology, 2022)
Background Interstitial lung disease (ILD) is frequently observed in anti-melanoma differentiation-associated protein 5 (MDA5) antibody positive dermatomyositis (DM) and anti-synthetase syndrome (ASS), where they often develop a rapidly progressive ILD (RP-ILD) leading to poor prognosis. Objective The aim of this study was to construct multivariable prediction risk factors for rapid progressive ILD (RP-ILD) in anti-MDA5 positive DM (MDA5+DM) and ASS. Methods 333 idiopathic inflammatory myopathy (IIM) associated ILD patients were studied retrospectively. Risk factors for RP-ILD in MDA5+DM and ASS patients were identified by univariate and multivariable logistic regression analysis. The mortality was assessed using Kaplan-Meier analysis. Results RP-ILD was more prevalent in MDA5+DM patients than ASS patients. MDA5+DM patients with RP-ILD had significantly lower survival rates than those in ASS patients. The independent risk factors for RP-ILD in MDA5+DM patients were fever (OR 3.67, 95% CI:1.79-7.52), lymphopenia (OR 2.14, 95% CI:1.01-4.53), especially decreased levels of CD3+T cells (OR 2.56, 95% CI:1.17-5.61), decreased levels of CD3+CD4+ T cells (OR 2.80, 95% CI:1.37-5.73), CD3+CD8+T cells (OR 2.18, 95% CI:1.05-4.50), elevated CD5-CD19+ B cells (OR 3.17, 95% CI:1.41-7.13), elevated ALT (OR 2.36, 95% CI:1.15-4.81), high lactate dehydrogenase (LDH) (OR 3.08, 95% CI:1.52-6.27), hyper-ferritin (OR 4.97, 95% CI:1.97-12.50), elevated CEA (OR 2.28, 95% CI:1.13-4.59), and elevated CA153 (OR 3.31, 95% CI:1.50-7.27). While the independent risk factors for RP-ILD in ASS patients were elevated CEA (OR 5.25, 95% CI: 1.73-15.93), CA125 (OR 2.79, 95% CI: 1.10-7.11) and NSE (OR 4.86, 95% CI: 1.44-16.37). Importantly, serum ferritin>2200ng/ml predicted patient's death within half a year in MDA5+DM patients with RP-ILD, but not in ASS patients. Conclusions There were significant different mortality and multivariable risk factors for RP-ILD in MDA5+DM patients and ASS patients. Potential clinical benefits of using these different risk factors deserve assessment of severity and prognosis in IIM patients.